The Content Analysis of the Research Papers on Language Learning Strategies - Pola Tahseen Mohammed; Manaf Basil Raewf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aimed to analyse the recent trends of language learning strategies in English Language Teaching (ELT) domain. Understanding and effective utilization of these learning strategies is vital in ELT. Content analysis approach has been chosen in order to provide a better idea of strategies used for future researcher and academic practitioner involve in English language learning and teaching. Content analysis are the best way to provide a bigger picture of any research area. A (45) number of articles have been analysed to define criteria in the research. The findings provide a clear picture of research approach, sample size, participants’ profile, analysis technique and data collection instruments adopted by previous authors from their papers conducted study on Language Learning Strategies (LLS).